Hypothalamic resting-state functional connectivity and self-evaluated aggression in young adults - Yao, Yuxing Jared; Chen, Yu; Li, Chiang-Shan R. (Journal of psychiatric research, 2025)
The hypothalamus plays a pivotal role in supporting motivated behaviors, including aggression. Previous work suggested differential roles of the medial (MH) and lateral hypothalamus (LH) in aggressive behaviors, but little is known about how their resting-state functional connectivity (rsFC) may relate to aggression in humans. We employed the data from the Human Connectome Project (HCP) and examined the rsFC's of LH and MH in 745 young adults (393 women). We also explored sex differences in the rsFC's. We processed the imaging data with published routines and evaluated the results of voxel-wise regression on the aggression score, as obtained from Achenbach Adult Self Report, with a corrected threshold. The analyses revealed significant rsFC's between the LH and clusters in the middle temporal and occipital gyri across all subjects and in the thalamus for men, both in negative correlation with the aggression score. The slope test confirmed sex difference in the correlation between the LH-thalamus rsFC and aggression score. No significant rsFC was observed for the MH. These findings suggest a role of the LH rsFC's and sex differences in the LH-thalamus rsFC in the manifestation of aggression in humans. The findings highlight the need for further research into sex-specific neural pathways in aggression and other related behavioral traits of importance to mental health.